Oral Squamous Cell Carcinoma in a Patient with Fanconi Anemia - Milla Huuhka; Aaro Turunen (Hindawi Limited, 2021)
Fanconi anemia (FA) is a rare autosomal recessive genetic disorder characterized by different types of malformations, skin lesions, bone marrow failure, and increased risk for both hematological malignancies and solid tumors, especially head and neck squamous cell carcinomas (HNSCC). FA patients may also display a low tolerance to oncologic treatments. The authors present a case of mandibular squamous cell carcinoma in a young FA patient. Because of the aggressive nature of the SCC and complex treatment options, we recommend a strict lifelong follow-up for all FA patients to detect early changes in the oral mucosa.